2020
DOI: 10.1080/21678421.2020.1760889
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the needs of people with ALS: a national survey of patients and caregivers

Abstract: Objective: Amyotrophic lateral sclerosis (ALS) has profound effects on people with ALS (PALS) and caregivers. There is a paucity of research detailing and comparing PALS and caregiver day-today perspectives of ALS. Methods: A survey developed collaboratively by The ALS Association and a panel of experts in ALS care was designed to broadly sample the experience of PALS and caregivers with respect to physical and emotional symptoms, the efficacy of treatment approaches, and goals for future treatments. Specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 52 publications
3
18
0
Order By: Relevance
“…Looking at the consequential health damages in half of our caregiver sample and restrictions of employment in one-third, we found that caregiving caused high individual but also socioeconomic costs. This is in line with rates of health damages in consequence of caregiving in previous reports [ 49 , 53 , 68 , 69 ]. Importantly, medical professionals need to be aware of the fact that caregivers need to be given proactive support to prevent those consequences: often, they are trapped in their daily duties, put their own needs last, or even feel as though they have no right to respect their own load limit in the face of their relatives terminal disease and—as reported in our sample—feel not strong enough to strive for help [ 52 , 57 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Looking at the consequential health damages in half of our caregiver sample and restrictions of employment in one-third, we found that caregiving caused high individual but also socioeconomic costs. This is in line with rates of health damages in consequence of caregiving in previous reports [ 49 , 53 , 68 , 69 ]. Importantly, medical professionals need to be aware of the fact that caregivers need to be given proactive support to prevent those consequences: often, they are trapped in their daily duties, put their own needs last, or even feel as though they have no right to respect their own load limit in the face of their relatives terminal disease and—as reported in our sample—feel not strong enough to strive for help [ 52 , 57 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is of great importance, as many patients and their caregivers are afraid of a painful suffocation, and this fear is associated with a wish for assisted suicide [ 48 ]. In this context, holistic palliative care has two tasks: first, to release patients and caregivers from this fear by providing information and emotional support, and second, to release or better prevent burdening symptoms by providing palliative medical support [ 46 , 48 , 49 ]. The small but relevant percentage of our patients dying with burdening symptoms illustrates that PPC alone cannot always provide such sufficient release.…”
Section: Discussionmentioning
confidence: 99%
“…QoL is defined as the general well-being of a person, and it includes the individual’s perception of their physical, social, and psychological state 3 . It has previously been observed that both the patient and next of kin are affected by ALS in terms of their QoL 4 , 5 , and some studies have found the psychological distress experienced by caregivers to have been even higher than that of PALS 6 , 7 . Knowledge of the factors that are associated with the caregivers’ QoL can lead to more tailored support for them.…”
Section: Introductionmentioning
confidence: 99%
“…In Ireland, QoL of caregivers of PALS was associated with caregiver burden, anxiety and depression 12 , but in a study of spousal ALS caregivers, family, hobbies and social activities were reported as the main contributors to improved QoL 7 . Fatigue has been referred to as a symptom that was present for both PALS and caregivers, but the small number of available treatments and the uncertainty that surrounds their efficacy are currently a challenge 6 . In our previous work we identified features that are predictive of QoL in PALS 13 , and we used a small subset of these factors in the development of an explainable model to alert clinicians when a patient is at risk of low QoL 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low incidence rates of ALS, research related to this disease and patient quality of life is sparse and only recently have there been efforts to explore these topics [4], [5], [6]. Over the past decade, there has been an increase in studies exploring the care needs and services provided to ALS patients and caregivers (e.g., [7], [8], [9], [10]).…”
Section: Introductionmentioning
confidence: 99%